BRIDGING LEADERSHIP AND INNOVATION: MAPPING THE EVIDENCE ON TRANSFORMATIONAL LEADERSHIP AND INNOVATIVE WORK BEHAVIOR - Jadmiko, Purbo; Anggraeni, Ade Irma; Purnomo, Ratno (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This systematic literature review synthesizes empirical evidence on the relationship between transformational leadership and innovative work behavior (IWB) across organizational contexts. Analyzing 11 high-quality studies from Scopus Q1 and Q2 journals (2018-2023), we identified three key findings: First, transformational leadership consistently enhances IWB through psychological empowerment, intellectual stimulation, and individualized consideration. Second, the strength of this relationship depends on mediators (trust, knowledge sharing) and moderators (work environment, cultural context). Third, measurement approaches for IWB vary significantly across sectors, with most studies employing quantitative methods such as the Innovation Behavior Inventory. The review reveals important geographical patterns, with substantial contributions from Asian researchers. We highlight critical gaps in current research, including inconsistent operationalization of IWB and insufficient attention to sector-specific dynamics. Our findings suggest that organizations can foster innovation by developing transformational leaders while creating supportive environments. Future research should focus on developing cross-cultural IWB measures and examining underrepresented sectors. This study contributes to leadership and innovation literature by providing a comprehensive, evidence-based framework for understanding how transformational leadership drives workplace innovation.